Characterisation of two aphid picorna-like viruses - Williamson, Carolyn (Department of Molecular and Cell Biology, 2017)
A new aphid virus, aphid lethal paralysis virus (ALPV), was isolated from laboratory-propagated Rhopalosiphum padi aphids co-infected with R. padi virus (RhPV). ALPV and RhPV were separated and ALPV was characterised in detail. Virions are isometric with a diameter of 26 nm, a sedimentation coefficient of 164 Sand a density in CsCl of 1.34 g/ml. Virions contain a 9.7 kb polyadenylated, singlestranded RNA and three major proteins with molecular weights of approximately 30 kilodaltons. By characterising RhPV further, two additional putative capsid proteins were found, an RNA poly(A) tract was detected and an RNA size of 10 kb was determined. A South African isolate of RhPV (RhPVoFs) was found to be serologically identical but physically distinct from a USA isolate. Complementary DNA was synthesized from RhPVOFS RNA and cloned into the plasmid vector, pBR322. This clone was used for the detettion of virus in aphids. ALPV and RhPV are serologically unrelated. ALPV is serologically distantly related to two insect picornaviruses, cricket paralysis virus (CrPV) and Drosophila C virus. No nucleic acid homology was detected between ALPV cDNA and CrPV by dot-blot hybridization. ALPV is serologically unrelated to seven other insect picornalike viruses. RhPV is serologically unrelated to any of the above mentioned viruses. ALPV and RhPV RNAs were efficiently translated in rabbit reticulocyte lysate into high molecular weight polypeptides, the sum of which exceeded the coding capacity of the genomes. Putative capsid precursor proteins of ALPV and RhPV were identified by immunoprecipitation. ALPV translation products were post-translationally cleaved as demonstrated in pulse-chase experiments and in experiments using a translation inhibitor. The efficiency of cleavage was concentration-dependent indicating the action of a protease. In parallel experiments with RhPV RNA, no evidence of post-translational cleavage was observed. In a survey of aphids collected in South Africa, ALPV and RhPV were detected in aphids from two major small-grain producing areas. Both viruses were found to naturally infect most of the cereal aphid species found in this country. ALPV and RhPV infections of R. padi resulted in a marked reduction in longevity and fecundity relative to uninfected aphids. Both viruses were found to be horizontally and vertically transmitted through aphid populations, and aphid host plants and aphid predators could be implicated in virus dissemination. ALPV and RhPV have many properties in common with each other as well as with insect and mammalian picornaviruses. Based on this data, it is proposed that ALPV and RhPV be classified into the picornavirus group (family Picornaviridae).